The Influence Of Job Design, Leadership, And Motivation On The Performance Of Service And Technical Officers PT. Razza Prima Transformer at PT. PLN Medan - Sri Rahayu Sri Rahayu; Ocdy Amelia; Muhtidun Hariz; Irvan Malay (International Journal of Society and Law, 2024)
This study aims to analyze the influence of job design, leadership, and motivation on the performance of service and technical officers at PT. Razza Prima Transformer who works at PT. PLN Medan. Job design is concerned with the way tasks are defined, organized, and mapped out in the work performed. Leadership focuses on the leadership style applied by managers or supervisors in organizations. Motivation involves factors that drive individuals to achieve goals and improve their performance. The research method used is a survey using questionnaires as a data collection instrument. The sample of this study consisted of service and technical officers at PT. Razza Prima Transformer who works at PT. PLN Medan. The collected data were analyzed using multiple linear regression analysis techniques. The population in this study was all Yantek officers totaling 110 people, while the sample of the population was 86 people. Data analysis techniques in this study use Data Quality Test, Classical Assumption Test, Multiple Linear Regression, and Hypothesis Test. Data processing in this study used SPSS software program version 25. It is partially known that job design, leadership, and motivation each have a positive and significant influence on the performance of Yantek officers at PT. Razza Prima Transformer Medan. It is simultaneously known that job design, leadership, and motivation each have a positive and significant influence on the performance of Yantek officers at PT. Razza Prima Transformer Medan